(2x^2 + 4x + 6) - (-3x - 5x^2 + 4)
The negative sign separating the expressions is just multiplying the rightmost expression by -1.
(2x^2 + 4x + 6) + (3x + 5x^2 - 4)
Now, let's add together terms that share the same variable.
2x^2 + 5x^2 = 7x^2
4x + 3x = 7x
6 + (-4) = 2
Let's combine each of these terms into one expression.
7x^2 + 7x + 2 is the final answer.
Answer:
74
x
+
185
Step-by-step explanation:
Answer:
The iron weighed 1/12 pound more than the aluminum.
Step-by-step explanation:
The weight of the aluminum is given as 1/2 pound. But that can also be written as 6/12 pound.
This is a subtraction problem (subtracting fractions...so also a common denominator problem)
In order to subtract fractions you have to get a common denominator.
7/12 - 1/2
= 7/12 - 6/12
= 1/12
The iron is 1/12 pound heavier than the aluminum.
Answer:
y = 2x - 7
Step-by-step explanation:
To find the line equation we assume that its form is y = m*x + b. Where m is the slope and b is the independent variable that intercepts the Y axis.
If we have two points as P1=(x1,y1) and P2=(x2,y2) we can use the slope formula as:
m = (y2-y1)/(x2-x1)
The points given are P1=(7,7) and P2=(2,-3), then the using the slope formula we obtain:
m = (-3-7)/(2-7)
m = (-10)/(-5)
m = 2
By now the equation is y = 2x + b. To find the value of b we have to replace in the equation any point, in this case i am using P2:
-3 = 2*(2) + b
-3 = 4 + b
-3 -4 = b
-7 = b
Therefore the equation of the line is:
y = 2x - 7